HIGH PRESSURE WATER JET EFFECT ON THE PROPERTIES OF COAL WINNING MACHINE CUTTING COAL - ZHAO LiJuan; MAO Zhen (Jixie qiangdu)
To explore the damage of water jet to coal wall,built up the finite element calculation model of water jet breaking coal,applying software ANSYS/ls-dyna is used to numerically simulate the process of water jet breaking coal,the results show that the coal wall impact damage is most serious,the center around the center of coal wall damage is small,water jet shock wave attenuation faster. To explore the influence of different velocity of water jet to coal wall injury,the different velocity of water jet coal process in numerical simulation,the results show that with the increase of flow velocity,the stress of the coal wall are also increase,but the impact damage range is not big,around the center shows that increasing the velocity of shock wave attenuation speed. To explore water jet,affect the performance of coal winning machine cutting coal shearer drum is established in the presence of water jet conditions they finite element calculation model of coal,the two conditions of numerical simulation for the process of cutting coal,the results show that: under the condition of water jet and cutting tooth stress decreases,and with the increase of water jet velocity,the cutter tooth stress decreases,when the water jet velocity of 300 m/s,water jet assisted cutting coal and has good effect.